Copper electrode material and method for preparing copper electrode for silicon solar cell using the same

By using copper electrode materials composed of copper wire, tin bismuth alloy and modified rosin, the problem of high cost and insufficient conductivity of silver electrodes in silicon solar cells is solved, and the low volume resistance and high oxidation stability of copper electrodes are achieved, reducing production costs and technical difficulties.

CN119541924BActive Publication Date: 2025-04-01SICHUAN MELKO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510083754.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-01
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The high cost and insufficient conductivity of silver electrodes in existing silicon solar cells, especially under low temperature process conditions, leads to exposure and oxidation of copper cores during sintering of silver-clad copper paste, and the resistance increases, and the silver consumption problem cannot be completely solved.

Method used

The copper electrode material composed of copper wire, tin bismuth alloy and modified rosin is used to improve its oxidation resistance and adhesion through chemically modified rosin, and a copper electrode of silicon solar cell is prepared through layer-by-layer assembly technology to reduce body resistance and interface contact resistance.

Benefits of technology

The low body resistance and high oxidation stability of copper electrodes are achieved, and the adhesion and interface contact resistance are improved during the melt welding process, reducing production costs and technical difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of silicon solar cells, and specifically relates to a copper electrode material and a method for preparing a copper electrode of a silicon solar cell using the same, wherein the copper electrode material comprises the following components: copper wire, tin-bismuth alloy, and modified rosin, and the preparation method of the modified rosin is: first, polyethylene glycol and aniline phenylacetic acid are used as raw materials, and aniline-modified polyethylene glycol is obtained by esterification reaction; then, rosin and acrylic acid are used as raw materials, and D-A addition reaction is used to obtain acrylic acid-modified rosin; finally, aniline-modified polyethylene glycol and acrylic acid-modified rosin are used as raw materials, and esterification reaction is used to obtain. The present invention also provides a method for preparing a copper electrode of a silicon solar cell using the copper electrode material, and a modified rosin layer, a tin-bismuth alloy layer, and a modified rosin layer are sequentially coated on the surface of the copper wire. The copper electrode provided by the present invention has lower body resistance and better oxidation stability, and also has excellent adhesion and lower interface contact resistance when the copper electrode is melt-welded to the surface of the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon solar cells, and in particular relates to a copper electrode material and a method for preparing a copper electrode for a silicon solar cell by using the copper electrode material. Background Art

[0002] Crystalline silicon solar cells are the mainstay of the photovoltaic industry. Among them, photovoltaic silver paste is the core auxiliary material for preparing the metal silver electrode of photovoltaic cells, which will directly affect the photoelectric performance of the cell. The cost of silver paste accounts for about 35% of the non-silicon cost of photovoltaic cells, which is the largest non-silicon cost of photovoltaic cells. Taking heterojunction (HJT) cells as an example, HJT cells use low-temperature processes due to film layer reasons, and can only use low-temperature silver paste. Low-temperature silver paste is a mixture of pure silver and organic matter, and has poor conductivity, so more silver paste is consumed. As a metal with electrical conductivity second only to silver, copper has the potential to replace silver electrodes in silicon-based solar cells.

[0003] The patent with application number CN201410430309.4 provides a silver-coated copper slurry for silicon solar cell electrodes. The silver-coated copper powder of the invention is a spherical fine metal powder with copper as the core, silver as the shell, and an intermediate layer of copper-tin-silver alloy. It is prepared by step-by-step reduction of copper sulfate, stannous sulfate and silver nitrate solution under alkaline conditions using glyoxylic acid or glyoxal as a reducing agent, thereby reducing the use of metallic silver and the cost of conductive slurry raw materials. A small amount of nano silver powder and silicone coupling agent additives are added to effectively prevent oxidation of the inner core copper, thereby improving the stability and reliability of the conductivity of the silver-coated copper powder. However, the slurry needs to be sintered at a temperature of 700-800°C. When the silver coating layer is uneven or thin, the copper core may be exposed during the sintering process, resulting in oxidation, which in turn leads to an increase in the resistance of the silver-coated copper slurry. Moreover, the process provided by the invention still cannot completely solve the problem of silver consumption. The patent with application number CN202110678201.7 provides a low-temperature copper electrode slurry, which is printed on the dielectric sheet of the ceramic capacitor and sintered at a temperature of 480-520°C in a nitrogen environment to form a copper electrode. This process helps to reduce energy consumption and manufacturing costs. However, preparing pure copper particles with micro-nano size and dispersing them into liquid slurry is a technology with a high threshold. The preparation process requires fine control of the reaction conditions to obtain copper particles of specific size and morphology, which increases the complexity of the process. Dispersing pure copper particles into liquid slurry requires ensuring uniform distribution of particles to avoid agglomeration, which requires special dispersion technology and processes, further increasing production costs and technical difficulties. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a copper electrode material and a method for preparing a copper electrode for a silicon solar cell using the same. The obtained copper electrode has lower body resistance and better oxidation stability, and also has excellent adhesion and lower interface contact resistance when the copper electrode is melt-welded to the surface of a substrate.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] A copper electrode material, comprising the following components: copper wire, tin-bismuth alloy, and modified rosin; the copper wire is red copper wire; the mass ratio of tin to bismuth in the tin-bismuth alloy is 40-45:55-60;

[0007] The preparation method of the modified rosin is as follows:

[0008] S1. Disperse polyethylene glycol in N,N-dimethylformamide, raise the temperature to 95-115° C. under stirring, react for 1-2 hours, then lower the temperature to 90-110° C., add anilinoacetic acid and p-toluenesulfonic acid, continue stirring and reacting for 6-9 hours, cool to room temperature, and purify to obtain aniline-modified polyethylene glycol;

[0009] S2. In a nitrogen atmosphere and under stirring conditions, add rosin and hydroquinone to a reactor, raise the temperature to 150-180°C, react for 30-50 minutes, then raise the temperature to 180-200°C, add acrylic acid dropwise, and complete the addition within 0.5-1.5 hours, then raise the temperature to 210-230°C, continue the reaction for 1.5-3.5 hours, lower the temperature to 170°C, discharge the material, and obtain acrylic acid-modified rosin;

[0010] S3. Under nitrogen atmosphere and stirring conditions, add the acrylic acid-modified rosin obtained in step S2 into a reactor, raise the temperature to 205-225° C., then add the aniline-modified polyethylene glycol obtained in step S1, react for 4-6 hours, then lower the temperature to 130-140° C., continue the reaction for 0.5-1.5 hours, discharge the material, and obtain modified rosin.

[0011] Rosin is a natural surfactant that can effectively remove oxides from the soldering surface and help the solder adhere better. It is an early soldering auxiliary material, mainly helping to remove oxides from pads during the soldering of circuit board parts. Tin-bismuth alloy is a metal alloy that is commonly used to make solder. After melting, this alloy can melt the pins of the component to the metal pads or holes on the circuit board to establish a conductive connection. Tin-bismuth alloy can be used as the main component of solder and used together with flux to improve the efficiency and quality of soldering. In some flux formulations, rosin can be used together with tin-bismuth alloy, with rosin as the base material of the flux and tin-bismuth alloy as the main component of the solder. This combination can provide good wettability during the soldering process while reducing the generation of oxides and improving the reliability of soldering. Rosin is mainly composed of resin acid, which is a type of monocarboxylic acid with a tricyclic phenanthrene skeleton and two double bonds. Due to the reactivity of the double bonds, rosin is easily isomerized and is relatively sensitive to the oxidation of air. It is easily oxidized by oxygen in the atmosphere, especially at higher temperatures or in powder form, which will affect the performance of rosin. Chemical modification of rosin is one of the effective means to improve its performance. The present invention first uses polyethylene glycol and anilinophenylacetic acid as raw materials to obtain aniline-modified polyethylene glycol through esterification reaction; then uses rosin and acrylic acid as raw materials to obtain acrylic acid-modified rosin through DA addition reaction; finally uses aniline-modified polyethylene glycol and acrylic acid-modified rosin as raw materials to obtain modified rosin through esterification reaction.

[0012] In order to functionalize the rosin, the mass ratio of polyethylene glycol, anilinoacetic acid and p-toluenesulfonic acid in step S1 is 100:2.0-2.6:0.4-0.6, and the mass volume ratio of polyethylene glycol to N,N-dimethylformamide is 0.07-0.11 g / mL; the mass ratio of rosin, hydroquinone and acrylic acid in step S2 is 10:0.3-0.4:2.4-2.8; and the mass ratio of acrylic acid-modified rosin and aniline-modified polyethylene glycol in step S3 is 15:27-33.

[0013] The method for preparing the copper electrode of a silicon solar cell by using the copper electrode material comprises sequentially coating the surface of a copper wire with a modified rosin layer, a tin-bismuth alloy layer, and a modified rosin layer.

[0014] Furthermore, the thickness of the modified rosin layer is 2-4 μm; the thickness of the tin-bismuth alloy layer is 8-12 μm; and the diameter of the copper wire is 30 μm.

[0015] The present invention has the following beneficial effects:

[0016] The present invention utilizes chemical reaction to graft diphenylamine, acrylic acid, and polyethylene glycol into the molecular structure of rosin to obtain modified rosin. Diphenylamine can fully exert its antioxidant effect by removing free radicals, chain transfer, improving physical anti-oxidation penetration ability, improving thermal oxidation stability, etc., thereby improving the antioxidant performance of modified rosin, effectively protecting the composite material from oxidation damage, and extending the service life of the material. In addition, diphenylamine can also improve the activity of rosin flux, thereby improving welding efficiency and quality; the introduction of acrylic acid can reduce the double bond active sites in the molecular structure of rosin, further improving its antioxidant performance, and the synergistic effect of acrylic acid and polyethylene glycol can also effectively increase the bonding force of modified rosin, thereby enhancing the adhesion of the composite material on the substrate. The present invention uses modified rosin and tin-bismuth alloy in a compound, which can improve the fluidity and wettability of the composite solder during melt welding, making the welding tighter, thereby effectively reducing the interface contact resistance between the copper electrode and the substrate.

[0017] The present invention prepares a silicon solar cell copper electrode through non-liquid slurry technology and layer-by-layer assembly technology. The copper electrode has low body resistance and good oxidation stability. When the copper electrode is melted and welded to the surface of a substrate, it also has excellent adhesion and low interface contact resistance. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] Polyethylene glycol, model PEG800, density 1.27g / cm³, brand Huijinchuan; rosin, first grade, model LTHG-234, brand Blueprint Chemical; tin-bismuth alloy, purity ≥99.9%. The raw materials used in the following examples are all common commercially available products.

[0020] Example 1

[0021] A copper electrode material, comprising the following components: copper wire, tin-bismuth alloy, and modified rosin; the copper wire is red copper wire; the mass ratio of tin to bismuth in the tin-bismuth alloy is 42:58;

[0022] The preparation method of the modified rosin is as follows:

[0023] S1. Disperse polyethylene glycol in N,N-dimethylformamide, raise the temperature to 105°C under stirring, reflux for 1.5h, then lower the temperature to 100°C, add anilinoacetic acid and p-toluenesulfonic acid, continue stirring for 8h, cool naturally to room temperature, separate the solid and liquid, take the solid, wash it three times with acetone, and vacuum dry it at 60°C for 12h to obtain aniline-modified polyethylene glycol. The grafting rate of polyethylene glycol measured by elemental analysis is 1.7%; wherein, the mass ratio of polyethylene glycol, anilinoacetic acid and p-toluenesulfonic acid is 100:2.3:0.5, and the mass volume ratio of polyethylene glycol to N,N-dimethylformamide is 0.08g / mL;

[0024] S2. Under nitrogen atmosphere and stirring conditions, add the crushed rosin and hydroquinone into a reactor, raise the temperature to 170°C, react for 40 minutes, then raise the temperature to 190°C, add acrylic acid dropwise, and complete the addition within 1 hour, then raise the temperature to 225°C, continue to react for 2.5 hours, naturally cool to 170°C, discharge, and obtain acrylic acid-modified rosin; wherein the mass ratio of rosin, hydroquinone, and acrylic acid is 10:0.35:2.6;

[0025] S3. Under nitrogen atmosphere and stirring conditions, add the acrylic acid modified rosin obtained in step S2 into a reactor, increase the temperature to 215° C., add the aniline modified polyethylene glycol obtained in step S1, react for 5 hours, then lower the temperature to 135° C., continue to react for 1 hour, discharge the material, and obtain modified rosin; wherein the mass ratio of acrylic acid modified rosin to aniline modified polyethylene glycol is 15:30.

[0026] A method for preparing a copper electrode of a silicon solar cell comprises the following steps: firstly, heating modified rosin to be completely melted (130°C for 20 minutes), and uniformly coating the surface of a copper wire with a modified rosin layer; then, heating a tin-bismuth alloy to be completely melted (140°C for 15 minutes), and uniformly coating the outer surface of the modified rosin layer with a tin-bismuth alloy layer; finally, heating the modified rosin to be completely melted (130°C for 20 minutes), and uniformly coating the outer surface of the tin-bismuth alloy layer with a modified rosin layer, to obtain a silicon solar cell; wherein the thickness of the modified rosin layer is 3 μm, the thickness of the tin-bismuth alloy layer is 10 μm, and the diameter of the copper wire is 30 μm.

[0027] Example 2

[0028] A copper electrode material comprises the following components: copper wire, tin-bismuth alloy, and modified rosin; the copper wire is red copper wire; the mass ratio of tin to bismuth in the tin-bismuth alloy is 45:60;

[0029] The preparation method of the modified rosin is as follows:

[0030] S1. Disperse polyethylene glycol in N,N-dimethylformamide, raise the temperature to 95°C under stirring, reflux for 2h, then lower the temperature to 90°C, add anilinoacetic acid and p-toluenesulfonic acid, continue stirring for 9h, cool naturally to room temperature, separate the solid and liquid, take the solid, wash it three times with acetone, and vacuum dry it at 60°C for 12h to obtain aniline-modified polyethylene glycol. The grafting rate of polyethylene glycol measured by elemental analysis is 1.6%; wherein the mass ratio of polyethylene glycol, anilinoacetic acid and p-toluenesulfonic acid is 100:2.6:0.6, and the mass volume ratio of polyethylene glycol to N,N-dimethylformamide is 0.07g / mL;

[0031] S2. Under nitrogen atmosphere and stirring conditions, add the crushed rosin and hydroquinone into a reactor, raise the temperature to 150°C, react for 50 minutes, then raise the temperature to 180°C, add acrylic acid dropwise, and complete the addition within 1.5 hours, then raise the temperature to 210°C, continue to react for 3.5 hours, naturally cool to 170°C, discharge, and obtain acrylic acid-modified rosin; wherein the mass ratio of rosin, hydroquinone, and acrylic acid is 10:0.4:2.8;

[0032] S3. Under nitrogen atmosphere and stirring conditions, add the acrylic acid modified rosin obtained in step S2 into a reactor, increase the temperature to 205° C., then add the aniline modified polyethylene glycol obtained in step S1, react for 6 hours, then lower the temperature to 130° C., continue to react for 1.5 hours, discharge the material, and obtain modified rosin; wherein the mass ratio of acrylic acid modified rosin to aniline modified polyethylene glycol is 15:33.

[0033] A method for preparing a copper electrode for a silicon solar cell is prepared according to the method described in Example 1, except that the thickness of the modified rosin layer is 2 μm, the thickness of the tin-bismuth alloy layer is 12 μm, and the diameter of the copper wire is 30 μm.

[0034] Example 3

[0035] A copper electrode material, comprising the following components: copper wire, tin-bismuth alloy, and modified rosin; the copper wire is red copper wire; the mass ratio of tin to bismuth in the tin-bismuth alloy is 40:55;

[0036] The preparation method of the modified rosin is as follows:

[0037] S1. Disperse polyethylene glycol in N,N-dimethylformamide, raise the temperature to 115°C under stirring, reflux for 1h, then lower the temperature to 110°C, add anilinoacetic acid and p-toluenesulfonic acid, continue stirring for 6h, cool naturally to room temperature, separate the solid and liquid, take the solid, wash it three times with acetone, and vacuum dry it at 60°C for 12h to obtain aniline-modified polyethylene glycol. The grafting rate of polyethylene glycol measured by elemental analysis is 1.9%; wherein the mass ratio of polyethylene glycol, anilinoacetic acid and p-toluenesulfonic acid is 100:2.0:0.4, and the mass volume ratio of polyethylene glycol to N,N-dimethylformamide is 0.11g / mL;

[0038] S2. Under nitrogen atmosphere and stirring conditions, add the crushed rosin and hydroquinone into a reactor, raise the temperature to 180°C, react for 30 minutes, then raise the temperature to 200°C, add acrylic acid dropwise, and complete the addition within 0.5 hours, then raise the temperature to 230°C, continue the reaction for 1.5 hours, naturally cool to 170°C, discharge, and obtain acrylic acid-modified rosin; wherein the mass ratio of rosin, hydroquinone, and acrylic acid is 10:0.3:2.4;

[0039] S3. Under nitrogen atmosphere and stirring conditions, add the acrylic acid modified rosin obtained in step S2 into a reactor, increase the temperature to 225° C., then add the aniline modified polyethylene glycol obtained in step S1, react for 4 hours, then reduce the temperature to 140° C., continue to react for 0.5 hours, discharge the material, and obtain modified rosin; wherein the mass ratio of acrylic acid modified rosin to aniline modified polyethylene glycol is 15:27.

[0040] A method for preparing a copper electrode for a silicon solar cell is prepared according to the method described in Example 1, except that the thickness of the modified rosin layer is 4 μm, the thickness of the tin-bismuth alloy layer is 8 μm, and the diameter of the copper wire is 30 μm.

[0041] Comparative Example 1

[0042] A copper electrode material is prepared according to the method described in Example 1, except that step S1 is omitted in the preparation process of modified rosin, and aniline-modified polyethylene glycol in step S3 is replaced by polyethylene glycol.

[0043] A method for preparing a copper electrode for a silicon solar cell is prepared according to the method described in Example 1.

[0044] Comparative Example 2

[0045] A copper electrode material is prepared according to the method described in Example 1, except that step S2 is omitted in the preparation process of modified rosin, and the acrylic acid-modified rosin in step S3 is replaced by rosin.

[0046] A method for preparing a copper electrode for a silicon solar cell is prepared according to the method described in Example 1.

[0047] Comparative Example 3

[0048] A copper electrode material is prepared according to the method described in Example 1, except that: in the preparation process of modified rosin, steps S1 and S2 are omitted, and the acrylic acid-modified rosin in step S3 is replaced by rosin, and the aniline-modified polyethylene glycol is replaced by polyethylene glycol.

[0049] A method for preparing a copper electrode for a silicon solar cell is prepared according to the method described in Example 1.

[0050] The following is a related performance test of the silicon solar cell copper electrodes prepared in Examples 1-3 and Comparative Examples 1-3. Antioxidation Performance Test The samples were placed at a temperature of 80°C and a humidity of 70% for 2 months, and the initial resistance R0 and the resistance R1 after the test of the samples were tested with a multimeter, and the resistance change rate was calculated, resistance change rate (%) = (R1-R0) / R0×100%. The sample is placed on a substrate (ITO glass) at a temperature of 140°C, and the sample is attached to the substrate through a melting and cooling process. Another copper electrode of the same size is attached in a parallel position using the same method. The multimeter is set to the ohm range, and the ends of the two copper electrodes are clamped with two-pole shark clips to measure the copper electrode body resistance, the copper electrode and substrate interface contact resistance, and the total resistance of the substrate resistance; the substrate resistance is obtained by touching the substrate surface with a two-pole electric pen (the distance between the electric pen is equal to the distance between the two copper electrodes); the copper electrode body resistance is obtained by touching the two ends of the copper electrode with a two-pole electric pen; the interface contact resistance between the copper electrode and the substrate is obtained by subtracting the total resistance, substrate resistance, and copper electrode body resistance. Adhesion test: The sample is placed on a substrate (ITO glass) at a temperature of 140°C, and a 1cm thick layer of copper is formed on the substrate through a melting and cooling process. 2 area (with equal lengths of unmelted samples retained at both ends), invert the substrate, connect standard weights to the ends of the sample, continue to add weights until the sample falls off the substrate, record the weight of the weights and calculate the adhesion. The above tests were repeated three times and the average value was taken. The test results are shown in Table 1. It can be seen from the data in Table 1 that compared with Comparative Examples 1-3, the silicon solar cell copper electrodes prepared in Examples 1-3 have excellent adhesion and interface contact resistance, and after the copper electrodes are placed at a temperature of 80°C and a humidity of 70% for 2 months, the resistance change rate is ≤4.6%, indicating that they have strong antioxidant ability.

[0051] Table 1 Test results of related performance of copper electrodes of silicon solar cells

[0052]

[0053] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A copper electrode material, characterized in that: The invention comprises the following components: copper wire, tin-bismuth alloy, and modified rosin; the copper wire is red copper wire; the mass ratio of tin to bismuth in the tin-bismuth alloy is 40-45:55-60; The preparation method of the modified rosin is as follows: S1. Disperse polyethylene glycol in N,N-dimethylformamide, raise the temperature to 95-115° C. under stirring, react for 1-2 hours, then lower the temperature to 90-110° C., add anilinoacetic acid and p-toluenesulfonic acid, continue stirring and reacting for 6-9 hours, cool to room temperature, and purify to obtain aniline-modified polyethylene glycol; S2. In a nitrogen atmosphere and under stirring conditions, add rosin and hydroquinone to a reactor, raise the temperature to 150-180°C, react for 30-50 minutes, then raise the temperature to 180-200°C, add acrylic acid dropwise, and complete the addition within 0.5-1.5 hours, then raise the temperature to 210-230°C, continue the reaction for 1.5-3.5 hours, lower the temperature to 170°C, discharge the material, and obtain acrylic acid-modified rosin; S3. Under nitrogen atmosphere and stirring conditions, add the acrylic acid-modified rosin obtained in step S2 into a reactor, raise the temperature to 205-225° C., then add the aniline-modified polyethylene glycol obtained in step S1, react for 4-6 hours, then lower the temperature to 130-140° C., continue the reaction for 0.5-1.5 hours, discharge the material, and obtain modified rosin.

2. The copper electrode material according to claim 1, characterized in that The mass ratio of polyethylene glycol, anilinoacetic acid and p-toluenesulfonic acid in step S1 is 100:2.0-2.6:0.4-0.

6.

3. The copper electrode material according to claim 2, characterized in that The mass volume ratio of the polyethylene glycol to N,N-dimethylformamide is 0.07-0.11 g / mL.

4. The copper electrode material according to claim 1, characterized in that The mass ratio of rosin, hydroquinone and acrylic acid in step S2 is 10:0.3-0.4:2.4-2.

8.

5. The copper electrode material according to claim 1, characterized in that The mass ratio of the acrylic acid-modified rosin to the aniline-modified polyethylene glycol in step S3 is 15:27-33.

6. A method for preparing a copper electrode for a silicon solar cell using the copper electrode material according to any one of claims 1 to 5, characterized in that: The surface of the copper wire is coated with a modified rosin layer, a tin-bismuth alloy layer and a modified rosin layer in sequence.

7. The method for preparing a copper electrode for a silicon solar cell using a copper electrode material according to claim 6, characterized in that: The thickness of the modified rosin layer is 2-4 μm.

8. The method for preparing a copper electrode for a silicon solar cell using a copper electrode material according to claim 6, characterized in that: The thickness of the tin-bismuth alloy layer is 8-12 μm.

9. The method for preparing a copper electrode for a silicon solar cell using a copper electrode material according to claim 6, characterized in that: The diameter of the copper wire is 30 μm.

Citation Information

Patent Citations

  • A silver-coated copper paste for silicon solar cell electrodes and its preparation method

    CN104157331B

  • Low-temperature copper electrode slurry and preparation method thereof

    CN113380440A

  • Electrode slurry and preparation method thereof

    CN118507102A

  • Production of rosin ester having excellent stability of color tone

    JP1995286139A